Pendampingan Guru Melalui Capacity Building dalam Rangka Optimalisasi Implementasi Penilaian Otentik Kurikulum 2013 (K-13) di MINU Curungrejo Kepanjen Malang - Nanik Ulfa; Aan Fardani Ubaidillah; Isna Nurul Inayati (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2019)
Kurikulum 2013’s is actually a government program that has been rolled out since then. However, in practice, there are still many teachers who have difficulties to implement it, especially in the case of the implementation of authentic assessments. This was experienced by the teachers of MINU Curungrejo Kepanjen Malang Regency. On this basis, the program focused on helping a teacher to improve understanding of Curriculum 2013 implementation (K-13) that relates to assessment. Various assessments must be carried out, namely; optical assessment, assessment of learning outcomes, Assessment of mastery learning, class assessment, and attitude assessment. The community service method in this activity uses two phases; the School Action Research and the Outcome Mapping. The results of the activities were carried out for six weeks starting from August to September 2018. They showed that intensive training and mentoring through School Action Research (SAR) and Outcome Mapping (OM) can improve the ability of teachers to implement the 2013 curriculum.